Cardiovascular patients in COVID‐19 era, a case series, an experience from a tertiary cardiovascular center in Tehran, Iran. Issue 12 (23rd July 2020) - Naderi, Nasim; Ansari Ramandi, Mohammad Mostafa; Baay, Mohammadreza; Hosseini, Zahra; Zanganehfar, Mohammad Esmaeil; Rabieie, Parham; Kamali, Monireh; Manshouri, Shirin; Moradnejad, Pardis; Asadian, Sanaz
Abstract: Different cardiovascular presentations of coronavirus disease 2019 can be seen because of the systemic involvement. Considering its new presentations, there is need for further studies regarding the mechanistic pathways involved. Abstract : Different cardiovascular presentations of coronavirus disease 2019 can be seen because of the systemic involvement. Considering its new presentations, there is need for further studies regarding the mechanistic pathways involved.